Edukasi dan Pencegahan Kekerasan terhadap Anak Berbasis Partisipasi Komunitas di Kecamatan Cibinong - Destiana Kumala; Guruh Herman Wasan; Molbi Febrio Harsanto; Rizky Arisandi; Awan Darmawan (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
Violence against children in Cibinong District is a critical issue demanding interventions beyond formal legal approaches. This community service aims to establish a sustainable child protection system using Participatory Action Research (PAR). The intervention targeted two primary ecological layers based on Bronfenbrenner’s theory: the family microsystem through Majelis Taklim Khairunnisa and the school mesosystem through SDIT Al Madinah. Through the cycle of mapping, planning, action, and reflection, this program sought to deconstruct social norms legitimizing violence. The results demonstrate three significant achievements: (1) A transformation in parenting styles from authoritarian to positive discipline, alongside the removal of the